The Effect of Reflexology on Blood Pressure in Pregnant Women with Hypertension - Utin Siti Chandra Sari; Emy Yulianti (JURNAL KEBIDANAN, 2024)
Nearly 95% of all maternal deaths occurred in low and lower-middle-class countries in 2020, and most were preventable. The direct causes of maternal death were 33.07% of hypertension disorders, 27.03% of obstetric bleeding, 15.7% of non-obstetric complications, 12.04% of other obstetric complications, 6.06% of infections in pregnancy, and 4.81% of other causes. This study aimed to explore the effect of reflexology on blood pressure in pregnant mothers with hypertension. A quasi-experimental design with a non-randomized pretest-posttest design was carried out in this study. The results showed that there was a statistically significant difference in the systolic blood pressure of hypertensive pregnant women before (147.30 ± 16,458) and after (130.55 ± 14,095) given reflexology massage therapy (p-value = 0.0001 (α 0.05); with a difference in pressure reduction up to 16.75 mmHg). In line with systolic blood pressure, Table 3 also shows that there is a statistically significant difference in the diastolic blood pressure of hypertensive pregnant women before (90.75 ± 8.571) and after (82.05 ± 8.912) given reflexology massage therapy (p-value = 0.001 (α 0.05); with a difference in pressure drop of up to 8.7 mmHg). Reflexology massage can be used as an alternative solution to lower blood pressure in pregnant women with hypertension. However, further research needs to be done on how reflexology massage can be applied properly to pregnant women to determine its impact on the mother and unborn baby.